Treatment options and anesthetic considerations for postnatal management of congenital lung malformation - Valeria Vlasceanu Coman; Gabriel Dragan; Vasilica Plaiasu; Mirela Pavelescu; Gheorghita Jugulete; Mihaela Oros (Amaltea Medical Publishing House, 2022)
Congenital lung malformations or CLM have resulted in an apparent increase in their frequency with the advances in fetal ultrasound technology and more widely available investigations in prenatal and postnatal periods. The advantage of an early diagnosis came together with the difficulty of the treatment decision, in special in the postnatal management of asymptomatic CLM. In this article, we summarized findings from current literature, with a particular emphasis on the therapeutic strategies. Management of infants for thoracic surgery represents a challenge not only for pediatric surgeon but also for anesthesiologists because of the anatomic and physiologic variations particularities. There are two main important parts that must be obtained: one lung ventilation and specific techniques for optimal pain management, distinguishing pediatric thoracic anesthesia from other pediatric anesthetic disciplines A comprehensive multimodal approach is necessarily followed by a long-term assessment of respiratory function of children who underwent surgery for lung resection.